2012
DOI: 10.1371/journal.pone.0027782
|View full text |Cite
|
Sign up to set email alerts
|

Copy Number Variations Due to Large Genomic Deletion in X-Linked Chronic Granulomatous Disease

Abstract: Mutations in genes for any of the six subunits of NADPH oxidase cause chronic granulomatous disease (CGD), but almost 2/3 of CGD cases are caused by mutations in the X-linked CYBB gene, also known as NAD (P) H oxidase 2. Approximately 260 patients with CGD have been reported in Japan, of whom 92 were shown to have mutations of the CYBB gene and 16 to have chromosomal deletions. However, there has been very little detailed analysis of the range of the deletion or close understanding of the disease based on this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
0
8
0
2
Order By: Relevance
“…So far, large deletions and duplications are considered uncommon genetic mutation events in CGD patients, probably due to the difficulty to detect multiple exon deletions/insertions with conventional methods (sequencing, PCR-SSCP, Southern blot). Recently, array comparative genomic hybridization (array CGH) and multiplex ligationdependent probe amplification were proposed for the detection of copy number variations (26,27) in CGD patients also. Stasia et al (27) reported two interesting cases of male XR-CGD patients, one with a 5.7-kb duplication spanning exons 6 and 8 of CYBB gene and the other with a deletion of the same region.…”
Section: Molecular Genetic Aspects Of Cgdmentioning
confidence: 99%
“…So far, large deletions and duplications are considered uncommon genetic mutation events in CGD patients, probably due to the difficulty to detect multiple exon deletions/insertions with conventional methods (sequencing, PCR-SSCP, Southern blot). Recently, array comparative genomic hybridization (array CGH) and multiplex ligationdependent probe amplification were proposed for the detection of copy number variations (26,27) in CGD patients also. Stasia et al (27) reported two interesting cases of male XR-CGD patients, one with a 5.7-kb duplication spanning exons 6 and 8 of CYBB gene and the other with a deletion of the same region.…”
Section: Molecular Genetic Aspects Of Cgdmentioning
confidence: 99%
“…The RPGR deletion has been reported as one type of retinitis pigmentosa (Cehajic-Kapetanovic et al, 2020). The proximity of the RPGR genes and the CYBB gene makes it a common co-existing disorder (11/16) (El Nemer et al, 2000;Peng et al, 2007;Yamada et al, 2010;Arai et al, 2012;Al-Zadjali et al, 2015;Gassner et al, 2017;Lhomme et al, 2020). In our case, X-linked retinitis pigmentosa, conerod dystrophy, and primary ciliary dyskinesia secondary to the RPGR gene mutation may manifest later in life.…”
Section: Discussionmentioning
confidence: 99%
“…Aproximadamente, el 10 % de los pacientes con la enfermedad presentan grandes deleciones que afectan uno o más exones del gen, e incluso estas pueden abarcar genes contiguos como el XK (síndrome de McLeod), el OTC (transcarbamilasa de ornitina), el DMD (distrofia muscular de Duchenne) y el RP (retinitis pigmentosa), entre otros (23,24). En el presente estudio no se pudieron establecer los puntos de quiebre 5' y 3' de la deleción, por lo tanto, no fue posible establecer el rango de genes afectados, incluidos los ya mencionados.…”
Section: Discussionunclassified